1968
DOI: 10.1126/science.160.3829.770
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine and Griseofulvin Reversibly Disrupt the Living Mitotic Spindle

Abstract: Using polarized light we have studied the effects of various mitotic poisons on mitotic spindles of living Pectinaria oocytes; we have studied fixed specimens with phase and electron microscopy. Vinblastine caused attrition and eventual disappearance of spindle structure as rapidly as did colcemid, and subsequent recovery from this treatment was at least as fast as that from colcemid. Griseofulvin, however, was easily the best agent for rapid, reversible, and repeated dissolution of the spindle. Agents that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(57 citation statements)
references
References 12 publications
4
53
0
Order By: Relevance
“…This action of colchicine was considerably enhanced by cold which is known to cause the reversible breakdown of microtubules into subunits (30,31). In the present study we have found that two other drugs, demecolcine and vinblastine, which disrupt microtubules (32,33) also inhibit the release of histamine from leukocytes. At the same time D20 which is known to favor the formation of microtubules in other cells (8,9) markedly potentiates antigeninduced histamine release.…”
Section: Resultsmentioning
confidence: 75%
“…This action of colchicine was considerably enhanced by cold which is known to cause the reversible breakdown of microtubules into subunits (30,31). In the present study we have found that two other drugs, demecolcine and vinblastine, which disrupt microtubules (32,33) also inhibit the release of histamine from leukocytes. At the same time D20 which is known to favor the formation of microtubules in other cells (8,9) markedly potentiates antigeninduced histamine release.…”
Section: Resultsmentioning
confidence: 75%
“…cal (1,12,16,23), biochemical, and physiological changes (5,(17)(18)(19)24) seen apparently as a direct consequence of this affinity between tubulin and the c-mitotic agents such as colchicine and the vinca alkaloids, vinblastine and vincristine. At the morphological level, a prominent manifestation of this affinity between some of the c-mitotic drugs and tubulin is seen in the destruction of the mitotic spindle and accumulation of cells in mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…No enhancement in binding is detected with the DEAE-filter disc method of labeled colchicine. Vinblastine is thought to stabilize the native configuration of the protein and preserve colchicine-binding activity without directly affecting the binding site (19)(20)(21)(22). When the decay of colchicine-binding activity was monitored at 370 by fluorescence, it was observed that the protein lost only 18'% of its initial binding in the presence of 0.2 mM vinblastine sulfate, whereas without vinblastine, 76% of binding activity was lost over the same 7-hr interval.…”
Section: Methodsmentioning
confidence: 99%